2019
DOI: 10.1111/ecc.13083
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on decision‐making about BRCA1/2 testing in Italian women

Abstract: Objective: In the era of cancer panel testing, new models of genetic counselling providing effective decision-making support are needed. As little is known about Southern European patients' and families' needs and experiences in this regard, we explored Italian women's experiences of clinical BRCA1/2 counselling and testing. Methods:We interviewed 19 Italian women with a strong family history but no personal history of cancer who had had clinical BRCA1/2 testing. Interviews were recorded and transcribed, and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…The focus on a diagnosis, which is a central theme of the present study, becomes even more important if it is connected to the theme of health innovation and to new possibilities introduced by genetic and scientific advances as well as new technologies to have more sensible and timely diagnoses. This change urges a deep understanding of the psychological effects of genetic diagnosis on individuals and their families (Rania and Migliorini, 2015; Alby et al, 2017; Battistuzzi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The focus on a diagnosis, which is a central theme of the present study, becomes even more important if it is connected to the theme of health innovation and to new possibilities introduced by genetic and scientific advances as well as new technologies to have more sensible and timely diagnoses. This change urges a deep understanding of the psychological effects of genetic diagnosis on individuals and their families (Rania and Migliorini, 2015; Alby et al, 2017; Battistuzzi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited awareness of genetic counselling, especially among young adults (Godino, Turchetti, Jackson, Hennessy, & Skirton, 2019). The decision to perform genetic testing often precedes counselling (Battistuzzi et al, 2019). The patients in this study seemed to be worried about hereditary cancer risk and most of them reported a high level of interest in the topic.…”
Section: Discussionmentioning
confidence: 99%
“…In order to ask for more attention and reflection and promote policy interventions for health and to consider the contribution of women to the health of the community (50). Moreover, the importance of attention to the involvement of people in their own health choices is now known (51, 52) and how the changes introduced by new health technologies make the relationship with health more predictable, which in this pandemic situation, on the other hand, seems to waver but, at the same time, require the person to internalize the idea of inevitable risk (53,54), which in this context becomes even more pervasive.…”
Section: A Gender Perspective: Women and The Covid-19 Pandemicmentioning
confidence: 99%